Effects of subinhibitory concentrations of nitroxoline on the surface properties of Escherichia coli - Latrache, H; Bourlioux, P; Karroua, M; Zahir, H; Hakkou, A (Folia microbiologica, 2000)
Nitroxoline (5-nitro-8-quinolinol; NIQ) at subinhibitory concentrations (sub-MIC) decreased the adherence of uropathogenic Escherichia coli to catheter surface and significantly enhanced cell surface hydrophobicity. The surface hydrophobicity increased in the presence of sub-MIC of NIQ and also in an excess of Mg2+. The effect of NIQ on the cell surface was not related to the bacteriostatic effect of this agent. The increase in nitrogen and decrease in phosphate content in the cell surface was found in the presence of NIQ. NIQ did not inhibit the expression of fimbriae.
Keywords: povrchové vlastnosti; katetrizace močového měchýře; infekce vyvolané Escherichia coli; Bacterial Adhesion; techniky in vitro; Escherichia coli Infections; Escherichia coli; nitrochinoliny; Urinary Catheterization; Urinary Tract Infections; elektronová mikroskopie; Cell Membrane; lidé; Nitroquinolines; infekce močového ústrojí; Humans; Surface Properties; Microscopy, Electron; buněčná membrána; bakteriální adheze; In Vitro Techniques